Practice-oriented learning as a way of professionalization of training future professionals in Ukraine - Maykovska, V. I. (Problems of Engineer-Pedagogical Education, 2018)
During the global Ukraine integration development of higher education in the country has to provide quality of professional training that makes the actual the orientation of higher educational establishments for the graduates’ ability to the practical implementation of heritage skills. In the article it was revealed the practice-oriented education as a way of professionalization of future specialists training, and its essence in high school. It was found that this approach is the subject of research of many national and foreign scholars, but its methodological, theoretical and technological aspects are not studied, structured and substantiated enough, and it is still insufficiently investigated. The article substantiates the expediency of practice-oriented approach in professional training and the of entrepreneurial initiative students’ experience formation on its basis. The study is based on the analysis the use of the category "practice-oriented approach in vocational training" in the specialist literature that allows state that scientists consider it as means of orientation of the educational process to the final product of vocational training - specified types of actions learned by students in the form of experience while working with educational information. This allows (during the process of professional training) to simulate the substantive content of professional activities and to provide the conditions of transformation of student learning activities into a professional specialist activity. The primary means implementation of practice-oriented approach is practice-oriented tasks and an indispensable condition of their application - compiling the correct conditions of these tasks. The implementation of practice-oriented approach requires teachers’ creation environment where students are able to discover and realize their interest to knowledge and make it the realized need for self-development, their professional and social adaptation. The desire to find a reasonable balance between academic and pragmatic elements of professional training is realized in attracting students to creation practice-oriented projects that are the result of individual or collective action by the clearly defined rules. The search results of the author for creating practice-oriented environment in Kharkov Trade and Economic Institute KNTEU is creation the program «Youth in business undertaking». The way of students participate in the program is the establishment of teams that implement their ideas into practice in the form of projects; documenting their activities in the form of reports; artistically and lucidly represent established and implemented projects to the jury - to potential employers and investors, representatives of the public institutions. Further scientific research of the author connected with the development of technology practice-oriented training at the background of implementation in the Kharkov Trade and Economic Institute KNTEU program "Youth in business undertaking '.